THE USE OF A DIODE LASER IN THE COMPLEX TREATMENT OF VARIOUS PATHOLOGICAL CHANGES IN THE MUCOUS MEMBRANE OF THE ESOPHAGUS - Makhsudov Maksud Tuymuradovich; Akhmedov Gayrat Keldibaevich; Gulamov Olimjon Mirzakhitovich; Khudaynazarov Utkir Rabbimovich; Dusiyarov Mukhammad Mukumbaevich (Journals Park Publishing, 2023)
This article is devoted to the diagnosis and treatment of one of the problems of modern medicine – the treatment of erosive and dysplastic changes of the mucous membrane in the esophagus. The data of the study and treatment of patients in the endoscopic department of the State Institution " RSSPMCS named after Academician V. Vakhidov" and in the diagnostic department of the Samarkand State Medical University. To improve the treatment parameters, laser radiation was used, which is part of modern complex treatment methods.
Keywords: erosion, dysplasia, complications, laser irradiation.